Anaplasma phagocytophilum-Related Defects in CD8, NKT, and NK Lymphocyte Cytotoxicity - Scorpio, Diana G.; Choi, Kyoung-Seong; Dumler, J. Stephen (Frontiers in Immunology, 2018)
Human granulocytic anaplasmosis (HGA), caused by the tick-transmitted Anaplasma phagocytophilum, is not controlled by innate immunity, and induces a proinflammatory disease state with innate immune cell activation. In A. phagocytophilum murine infection models, hepatic injury occurs with production of IFNγ thought to be derived from NK, NKT cells, and CD8 T lymphocytes. Specific A. phagocytophilum ligands that drive inflammation and disease are not known, but suggest a clinical and pathophysiologic basis strikingly like macrophage activation syndrome (MAS) and hemophagocytic syndrome (HPS). We studied in vivo responses of NK, NKT, and CD8 T lymphocytes from infected animals for correlates of lymphocyte-mediated cytotoxicity and examined in vitro interactions with A. phagocytophilum-loaded antigen presenting cells (APCs). Murine splenocytes were examined and found deficient in cytotoxicity as determined by CD107a expression in vitro for specific CTL effector subsets as determined by flow cytometry. Moreover, A. phagocytophilum-loaded APCs did not lead to IFNγ production among CTLs in vitro. These findings support the concept of impaired cytotoxicity with A. phagocytophilum presentation by APCs that express MHC class I and that interact with innate and adaptive immune cells with or after infection. The findings strengthen the concept of an enhanced proinflammatory phenotype like MAS and HPS disease states as the basis of disease and severity with A. phagocytophilum infection, and perhaps by other obligate intracellular bacteria.